Screening Tool for Older Persons' Appropriate Prescriptions in Japanese: Report of the Japan Geriatrics Society Working Group on "Guidelines for medical treatment and its safety in the elderly". Issue 9 (September 2016) - Kojima, Taro; Mizukami, Katsuyoshi; Tomita, Naoki; Arai, Hiroyuki; Ohrui, Takashi; Eto, Masato; Takeya, Yasushi; Isaka, Yoshitaka; Rakugi, Hiromi; Sudo, Noriko; Arai, Hidenori; Aoki, Hiroaki; et al.
Abstract: Aim: In 2005, the Japan Geriatrics Society published a list of potentially inappropriate medication that was an extract from the "Guidelines for medical treatment and its safety in the elderly 2005." The 2005 guidelines are due for a revision, and a new comprehensive list of potentially inappropriate medications is required. Methods: A total of 15 diseases, conditions and special areas related to their clinical care were selected. We originated clinical questions and keywords for these 15 areas, carried out a systematic review using these search criteria, and formulated guidelines applying the Grading of Recommendations Assessment, Development and Evaluation system advocated by Minds2014. If we did not find good evidence despite the drug being clinically important, we looked for evidence of efficacy and for disease‐specific guidelines, and incorporated them into our guidelines. Results: We selected 2098 articles (140 articles per area), and extracted another 186 articles through a manual search. We further added guidelines based on disease entity and made two lists, one of "drugs to be prescribed with special caution" and the other of "drugs to consider starting, " primarily considering individuals aged 75 years or older or those who are frail or in need of special care. Conclusions: New lists of potentially inappropriate medications and potential prescribing omissions called "Screening Tool for Older Person's Appropriate Prescriptions for Japanese" were constructed. We anticipate that future studies will highlight more evidence regarding the safety of high‐quality drugs, further improving the provision of appropriate medical care for the elderly.Geriatr Gerontol Int 2016: 16: 983–1001.